IN MEMORIAM: PROF. VIOLETA DIMOVA, THE FIRST DEAN OF THE FACULTY OF PHILOLOGY IN STIP (1955-2021) (PALIMPSEST / ПАЛИМПСЕСТ, 2021)
Professor Violeta Dimova passed away on the 7th of May 2021. She was the first dean and one of the founders of the Faculty of Philology in Shtip. The eleventh issue of the International Journal “Palimpsest” is dedicated to our dear professor and friend, Violeta Dimova.Professor Violeta Dimova will always remain in our memories for her humaneness, kindness, energy, persistence and combativeness in achieving all the goals she set for herself and passed on to us for the development and promotion of our Faculty of Philology.Rest in peace, our dear Vicky.From the colleagues at the Faculty of Philology in Shtip